2015
DOI: 10.1007/s12204-015-1624-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimal burn-in and preventive maintenance modeling with competing failure processes

Abstract: In this article, we assume that the product in the burn-in procedure only experiences continuous smooth degradation process, while in the field operation period the product experiences both continuous smooth degradation process and shock process. The shock process can cause the product not only traumatic failure, but also additional abrupt degradation damage. After the system reliability model and maintenance model have been proposed, the optimal burn-in setting and age replacement duration are obtained under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The crystal defects and internal stress field could be introduced by cold pre‐deformation. Actually, a great number of recent studies have been focused on the effect of pre‐deformation on the properties of various materials, including aluminum alloy, Zirconium alloy, shape memory alloys, FeMn damping alloy and Mn‐15 at% damping alloy . In all, the defects and internal stress distribution aroused by the pre‐deformation play a critical role in affecting the properties of the above alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal defects and internal stress field could be introduced by cold pre‐deformation. Actually, a great number of recent studies have been focused on the effect of pre‐deformation on the properties of various materials, including aluminum alloy, Zirconium alloy, shape memory alloys, FeMn damping alloy and Mn‐15 at% damping alloy . In all, the defects and internal stress distribution aroused by the pre‐deformation play a critical role in affecting the properties of the above alloys.…”
Section: Introductionmentioning
confidence: 99%
“…In all, the defects and internal stress distribution aroused by the pre‐deformation play a critical role in affecting the properties of the above alloys. Huang S.K et al found the stacking fault probability change caused by the deformation is attributes to the change of FeMn damping capacity. Tian Q et alreported the dependence of dislocation and retained strain energy on the reverse transformation temperature and heat of Mn‐15 at% alloy.…”
Section: Introductionmentioning
confidence: 99%